The analysis of the concept of vulnerability on the International legal framework on Human Trade - Pascoal, Rafaela Hilário (Debater a Europa, 2018)
The establishment of the Trafficking1 and the Smuggling Protocol2 has brought to the surface the importance of the concept of vulnerability. However, the Protocols have not given a precise definition to the concept of vulnerability, in order to perceive a practical application on legal grounds. In 2005, the Council of Europe tries to delimit the definition’s gap of such concept, through the Convention of Warsaw3, giving a more exact definition of the concept. The present article intends to analyse the evolution and the application of this concept on the international legal framework on Human trafficking and Smuggling of migrants.